Embedded discontinuities for 3D mode-I and mode-II failure modelling - Wells, Garth N.; Sluys, Lambertus J. (Computer Assisted Methods in Engineering and Science, 2000)
The incorporation of displacement discontinuities in finite elements is examined. The incorporation of displacement discontinuities allows the use of discrete constitutive models in a continuum framework in order to avoid the mesh sensitivity of classical continuum models when strain softening is introduced. The procedure for building discontinuities into finite elements is examined, as well as two classes of constitutive models for mode-I and mode-II failure analysis. The performance of the model is illustrated with three-dimensional examples.